Pengembangan Kurikulum dan Perencanaan Pembelajaran Yang Responsif Terhadap Tantangan Pendidikan Abad Ke-21 - Luthfi Adam Lubis; Ros Suryaningsih Ge'e; Zelma Azahra; Ratika Balqis Nst; Safran Safran (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study focuses on developing responsive curriculum and instructional planning to meet the challenges of 21st-century education. Collaboratively authored by students from the Islamic State University of North Sumatra, the research explores the background, theoretical foundations, and methodologies involved. The research underscores the need for adaptive strategies in curriculum development and learning planning. Utilizing a concise literature review, the authors identify gaps and emphasize the research's novelty. The methodology outlines the study design, participants, data collection, and analysis, including instrument validation. Findings and discussions provide a comprehensive analysis, integrating visuals for clarity. Implications, both theoretical and practical, offer valuable insights. The conclusion succinctly summarizes the findings and provides recommendations, contributing significantly to discussions on responsive education.